KEMAMPUAN PENGGUNAAN JODOUSHI-SOUDA PADA MAHASISWA TINGKAT III PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI PADANG - harviko lidra; Meira Anggia Putri; Damai Yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
This research is a quantitative descriptive research. The purpose of this study is to describe the ability in using“jodoushi ~ souda”,of 2016 5th semester students of Japan Language Education Studies Program at Padang State University. By using total sampling method, the population of this study is2016 5th semester students of Japan Language Education Studies Program at Padang State University.There are some indicators in order to achieve the objectives of this research, they are (1) find out how student's ability in making sentence of “souda” as “youtai”or as “denbun” based on images/pictures. (2) find out how student's ability in completing anincomplete sentence by choosing verb, adjective, or noun attached to “souda” as “denbun” or as“youtai”. (3) find out how student's ability in transforming the underlined words into “souda” as “denbun” or as“yotai”form based on the context of the sentence. The results of this research is the ability of using“jodushi~souda” as “denbun” is qualifying as honors with an average scoreis 99.56, while ability of using “jodushi~souda” as “youtai”isqualifying as more than enough qualifications with an average score is 64. So it can be concluded that the ability of using of “jodoushi ~ souda” as “denbun” is higher than the ability of “jodushi~souda” as “youtai”. Keywords: jodoushi, ~souda, denbun, youtai